The primary motivation of sexual homicide offenders in China: Was it for sex, power and control, anger, or money?. (20th May 2019) - Chan, Heng Choon (Oliver); Li, Feng; Liu, Sihai; Lu, Xuesong
Abstract: Background: Information on sexual homicides in China is scarce, particularly with respect to the offenders' primary motivation for the offence. Aims: Our aim was to examine how offence characteristics of sexual murderers relate to different primary motivations. Methods: The offender, victim, and offence characteristics of 67 sexual homicides, derived from police data of three regions and published case reports (1994–2017), were explored and compared according to offenders' primary motivation. Results: Heterosexual sexual homicides were committed by offenders who were mainly driven by power and control, sex, and anger, compared with slightly over half of those who motivated primarily by financial gain. Sexual murderers whose killing was mainly driven by sex, money, and anger were more likely to target strangers, whereas offenders who motivated primarily by power and control were more likely to target an intimate partner. Victim abduction was more frequently seen in offenders who were motivated predominantly by money than other motives. Relative to financial gain as primary motivation, sexual killers who were mainly driven by sex, power and control, and anger were more likely to mutilate their victim. Implications for practice: This study adds data to a field rarely studied anywhere and hardly at all in China. Findings may offer some help for criminal investigators who need to prioritise their investigative strategies. Once the individual is convicted and sentenced, they may help direct management and/or therapeutic strategies.